In Vitro Biological Activities of Drepanoalpha® Ethanolic Extract, A Justicia Secunda and Moringa Oleifera-Based Phytomedicine Proposed for The Symptomatic Treatment of Sickle Cell Disease - Benjamin Gbolo Zoawe; Amandine Nachtergael; Damien S. T. Tshibangu; Nicole M. Misengabu; Victoire Nsabatien; Patrick B. Memvanga; Dorothée D. Tshilanda; Jean-Paul K. N. Ngbolua; Pius T. Mpiana; Pierre Duez (Universitas Muhammadiyah Yogyakarta, 2023)
Sickle cell disease (SCD) is an autosomal recessive blood disorder characterized by red blood cells that assume an abnormal, rigid sickle shape under low-oxygen conditions. These sickle-shaped erythrocytes tend to lyse, aggregate, and obstruct small blood vessels, leading to major complications. The present study aims to investigate properties that may underlie the activity of Drepanoalphaâ, an antisickling herbal formulation developed in the Democratic Republic of Congo (DRC) for the prevention and symptomatic treatment of sickle cell disease crises. The Drepanoalpha® Ethanolic Extract (DEE) is a dry extract (drug-extract ratio, DER, 100/11) prepared from ethanol (96 %, v/v) percolation of a 1:1 mixture of 2 food plants, Justicia secunda Vahl and Moringa oleifera Lam. Sickling was classically measured by light microscopy on diluted washed erythrocytes obtained from homozygote patients; erythrocytes were treated with 2 % Na2S2O5 in the presence of DEE (suspension in 9 ‰ NaCl), 9 ‰ NaCl (negative control) or disodium cromoglycate (DSCG, positive control). For all tested conditions, the sickle hemoglobin polymerization, the Fe2+/Fe3+ ratio, and the median corpuscular fragility were measured by spectrophotometry. The DEE reversed sickling by 89.1 %, comparable to DSCG (87.7 %; 60.3 µg/mL), inhibiting sickle cell hemoglobin polymerization of 77.8 % and 74.4 %, respectively. The Fe2+/Fe3+ ratio was improved by 18.0 % for DEE and 15.9 % for DSCG. The median corpuscular fragility values were 0.602, 0.714, and 0.732 for NaCl 9 ‰, DSCG, and DEE, respectively. The measured in vitro parameters validate an effective antisickling effect of DEE and confirm the value of this improved traditional herbal formulation for the management of SCD.